An Improved Integrated Approach To Improving The Efficiency Of Energy Management Of Residential Buildings. - Aymatov Anvarbek Abdikholikovych; Khalimov Khabibullo Bakhtiyarjon ogli (Genius Journals, 2024)
This article brings information about an improved comprehensive approach to improving the efficiency of energy management of residential buildings, a comprehensive approach to improving the energy efficiency of buildings, methods for assessing the effectiveness of energy-saving solutions
Keywords: residential; building; energy; investments